Obsessive‐compulsive disorder and men's health. Part 2: Treatment and related sexual dysfunction. Issue 2 (23rd February 2023) - Conti, Dario; Pellegrini, Luca; Riaz, Maham; Mpavaenda, David; Sim, Alex; Fineberg, Naomi
Abstract : Obsessive‐compulsive disorder (OCD) commonly affects males and can manifest with a range of urological symptoms directly linked to the content of the OCD. In Part 1 of this article, the authors discussed the recognition and diagnosis of OCD. In Part 2 here, they consider its treatment and related sexual dysfunction.